Calibration of the flow in the channel of the whirling arm - Ashill, P. R.; Osbourn, E. W. (College of Aeronautics, 1969)
The calibration of the flow in the channel of the Whirling Arm is described and results for pitch yaw and wind speed are presented. These indicate that the flow is quite acceptable for the type of model tests envisaged.